TAXONOMY, BIOSTRATIGRAPHY AND BIOGEOGRAPHY OF THE PERMIAN MIZZIA-LIKE CALCAREOUS ALGAE (DASYCLADALES, CYCLOCRINACEAE) - Chuvashov B.I. (My University, 2001)
Algae with a wide range of morphological characters were assigned to the genus Mizzia that was established without an estimate of the taxonomic importance of its characters. We considered the morphology of twigs on the thallit (calcified part of the thallome) as a leading character and took into account some other morphological characters of this genus. As a result, the genus Mizzia (s. l.) was subdivided into several new genera: Mizzia (s. str.), Yabeites, Cornutella, and Bisertiella. The position of these genera in the taxonomic system of green algae, their biostratigraphy and biogeography are discussed.
Keywords: Permian; Mizzia; Paleozoic::Permian; Палеозой::Пермская